2009
DOI: 10.1002/hep.22790
|View full text |Cite
|
Sign up to set email alerts
|

The rtA194T polymerase mutation impacts viral replication and susceptibility to tenofovir in hepatitis B e antigen–positive and hepatitis B e antigen–negative hepatitis B virus strains #

Abstract: The rtA194T polymerase mutation is associated with partial tenofovir drug resistance and negatively impacts replication competence of HBV constructs. Viral replication, however, can be restored to WT levels, if these polymerase mutations occur together with precore or basic core promoter substitutions as found in HBeAg-negative hepatitis B. Patients with HBeAg-negative chronic HBV infection may therefore be at particular risk when developing drug resistance to tenofovir. Telbivudine or entecavir should be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 40 publications
9
107
1
1
Order By: Relevance
“…We did not find the mutation rtA194T which was proposed to be associated with tenofovir resistance by Amini-Bavil-Olyaee et al [16] The result of another large study from China [17] also supports our findings in this regard as they did not find this mutation. Our data is also consistent with another recent study by Chen et al [18] who found the mutations rtA181T and rtN236T from lemivudine and adefovir resistant patients, although we did not find rtN236T and rtA181T from our samples.…”
Section: Discussionsupporting
confidence: 85%
“…We did not find the mutation rtA194T which was proposed to be associated with tenofovir resistance by Amini-Bavil-Olyaee et al [16] The result of another large study from China [17] also supports our findings in this regard as they did not find this mutation. Our data is also consistent with another recent study by Chen et al [18] who found the mutations rtA181T and rtN236T from lemivudine and adefovir resistant patients, although we did not find rtN236T and rtA181T from our samples.…”
Section: Discussionsupporting
confidence: 85%
“…All constructs were confirmed by digestion analysis and direct sequencing (Applied Biosystems, Foster City, CA) (24). To generate HBeAg-negative vectors, the 1.28-fold HBV replication-competent plasmids harboring G1896A/C1858T PC and A1762T/ G1764A BCP mutations were used (2,24). The fragment containing the LAMresistant/immune escape mutant was excised by EcoRI and NcoI restriction enzymes (New England Biolabs, Ipswich, MA) and ligated into the same region within the PC and BCP plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the noncross-resistance between ETV and TDF, the use of ETV should be effective in these cases, either as mono-or combination therapy ( Table 2). In vitro data indeed demonstrated that ETV is effective against TDF-resistant strains (24,26). The situation might be more complex in patients with multiple drug-resistant mutations due to an extended treatment history.…”
Section: Tdf Resistance and Multi-drug Resistancementioning
confidence: 96%
“…In vitro, this rtA194T polymerase mutation is associated with a partial drug resistance against TDF. On the other hand, the rtA194T mutation impairs replication competence of HBV constructs in vitro, possibly explaining the low occurrence of this mutant in clinical practice (24).…”
Section: Tdfmentioning
confidence: 99%